2017
DOI: 10.3389/fmicb.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

The Social Life of Aeromonas through Biofilm and Quorum Sensing Systems

Abstract: Bacteria of the genus Aeromonas display multicellular behaviors herein referred to as “social life”. Since the 1990s, interest has grown in cell-to-cell communication through quorum sensing signals and biofilm formation. As they are interconnected, these two self-organizing systems deserve to be considered together for a fresh perspective on the natural history and lifestyles of aeromonads. In this review, we focus on the multicellular behaviors of Aeromonas, i.e., its social life. First, we review and discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 175 publications
(283 reference statements)
2
75
0
Order By: Relevance
“…The "signal" molecule in Gram-negative bacteria is N-acyl homoserine-lactone (AHL) and in Aeromonas, the AHL is able to modulate the host immune response [19,186,259]. Several studies have shown the importance of AHLs in regulating a range of biological functions such as biofilm formation, antibiotic production, and warming motility and the different QS systems harbor differences in their influences [260][261][262][263][264][265][266]. Chan et al [260] found in the whole genome of the strain A. veronii 159 sequences of QS-related genes, providing a model for exploring it roles in virulence and as a potential target for Aeromonas treatment.…”
Section: Quorum Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The "signal" molecule in Gram-negative bacteria is N-acyl homoserine-lactone (AHL) and in Aeromonas, the AHL is able to modulate the host immune response [19,186,259]. Several studies have shown the importance of AHLs in regulating a range of biological functions such as biofilm formation, antibiotic production, and warming motility and the different QS systems harbor differences in their influences [260][261][262][263][264][265][266]. Chan et al [260] found in the whole genome of the strain A. veronii 159 sequences of QS-related genes, providing a model for exploring it roles in virulence and as a potential target for Aeromonas treatment.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Chan et al [260] found in the whole genome of the strain A. veronii 159 sequences of QS-related genes, providing a model for exploring it roles in virulence and as a potential target for Aeromonas treatment. Talagrand-Reboul et al [266] focused their review on the knowledge of the biofilm and QS in Aeromonas, explaining that biofilm provides a high cell-density that allows interaction between bacteria with the QS systems in Aeromonas. That study also reported the possible role of this biofilm formation in mixed infections and should be further studied.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…; Talagrand‐Reboul et al . ). Aeromonas veronii PR was shown to form biofilm in both static and mobile conditions, with temperature affecting the process contrastively (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, bacterial surface components such as fimbriae and flagella provide CSH (Donlan ) and bacterial motility, which is closely related to the presence of these particular appendages, decisive for the attachment (Talagrand‐Reboul et al . ). In fact, micro‐organisms able to form biofilm usually exhibit one or more of the three main types of motility, depending on the presence of flagella (swimming and swarming) and type IV pili (twitching; Kearns ).…”
Section: Introductionmentioning
confidence: 97%